Managing a solo practice - Sharara, Fady I (Seminars in reproductive medicine, 2013)
Our health care system has been facing significant changes over the past 20 years with the introduction of health maintenance organizations plus the seismic changes associated with the introduction of the Patient Protection and Affordable Health Care Act and accountable care organizations. Lower reimbursements by health plans and the need for significant infrastructure investments in information technology such as electronic medical records have also put major financial and organizational strains on solo practices. Although it is unknown how these changes will have an impact on reproductive endocrinologists, consolidation and mergers seem to be on the rise in anticipation of the coming tsunami. Many solo physicians have cherished the freedom and opportunity of small practices, but it appears that the delivery system of the future will be dramatically different.